Farklı spor dallarındaki çocukların kemik mineral yoğunluklarının değerlendirilmesi - Çetiner, Elif (My University, 2005)
FARKLI SPOR DALLARINDAKİ ÇOCUKLARIN KEMİK MİNERAL YOĞUNLUKLARININ DEĞERLENDİRİLMESİ Adı ve Soyadı: ELİF ÇETİNER Danışmanın Adı: YRD.DOÇ.DR. İLHAN ODABAŞ EYLÜL 2002 SANS BEDEN EĞİTİMİ VE SPOR

Çalışmanın amacı; yüzme, tenis ve hentbol gibi farklı spor dallarıyla uğraşan, ergenlik öncesi dönemdeki çocukların (kız-erkek) kemik mineral yoğunluğunu değerlendirmektir. Araştırmaya; 1994-1995 doğumlu, pubertal olmayan, toplam 80 sağlıklı çocuk (40 kız-40 erkek) katılmıştır. Sporcu grup, en az 1 yıldır düzenli (haftada en az 2 defa) antrenman yapan 60 çocuktan (ortalama olarak her grup için 20 çocuk), kontrol grubu ise; 20 sedanter çocuktan oluşturulmuştur. Çocukların; boy, kilo, % yağ ve kemik mineral yoğunlukları ölçülerek, yapılan anket ile günlük kalsiyum miktarları belirlenmiştir. Boy için stadiometre, kilo için dijital tartı, % yağ ölçümlerinde skinfold kaliper ve Biyoelektriksel empedans yöntemleri; kemik yoğunluğu ölçümleri için ise, Ultrason yöntemi (Sunlight Omnisense 7000p-SOS) kullanılmıştır. Skinfold kaliper ile yapılan % yağ ölçümleri; Triceps, Biceps, Subscapular ve Suprailiac deri altı yağ kalınlığı alınarak, Durnin Womersley % yağ formülü ile hesaplanıp, dominant taraftan yapılmıştır. Kemik mineral yoğunluğu ölçümleri ise dominant olmayan tarafın radius ve tibia kemiklerinden yapılmıştır. Ölçümler; etik kurul onayı alındıktan sonra, Marmara Üniversitesi Hastanesinde, uzman doktorlar tarafından yapılmıştır. Sonuç olarak; 22 öğrenciden oluşan Kontrol Grubunun boy ölçümleri; 134.5 ± 4.8, 19 öğrenciden oluşan Yüzme Grubunun boy ölçümleri; 139.2 ± 5.9, 20 öğrenciden oluşan Hentbol Grubunun boy ölçümleri; 142.4 ± 5.09, 19 öğrenciden oluşan Tenis Grubunun boy ölçümleri; 139.5 ± 5.4 olarak ortalama değerleri bulunmuştur. 22 öğrenciden oluşan Kontrol Grubunun ağırlık ölçümleri; 30.5 ± 4.8, 19 öğrenciden oluşan Yüzme Grubunun ağırlık ölçümleri; 34.0 ± 5.8, 20 öğrenciden oluşan Hentbol Grubunun ağırlık ölçümleri; 37.5 ± 7.0, 19 öğrenciden oluşan Tenis Grubunun ağırlık ölçümleri; 33.7 ± 3.9 olarak ortalama değerleri bulunmuştur. 22 öğrenciden oluşan Kontrol Grubunun BIA ölçümleri; % 13.5, 19 öğrenciden oluşan Yüzme Grubunun BIA ölçümleri; % 16.1, 20 öğrenciden oluşan Hentbol Grubunun BIA ölçümleri; % 16.6, 19 öğrenciden oluşan Tenis Grubunun BIA ölçümleri; % 12.7 olarak ortalama değerleri bulunmuştur. 22 öğrenciden oluşan Kontrol Grubunun DW ölçümleri; % 20.7, 19 öğrenciden oluşan Yüzme Grubunun DW ölçümleri; % 20.1, 20 öğrenciden oluşan Hentbol Grubunun DW ölçümleri; % 22.03, 19 öğrenciden oluşan Tenis Grubunun DW ölçümleri; % 20.77 olarak ortalama değerleri bulunmuştur. 22 öğrenciden oluşan Kontrol Grubunun Günlük Kalsiyum Tüketimi Değerleri; 689.2 ± 187.7, 19 öğrenciden oluşan Yüzme Grubunun Günlük Kalsiyum Tüketimi Değerleri; 635.0 ± 262.3, 20 öğrenciden oluşan Hentbol Grubunun Günlük Kalsiyum Tüketimi Değerleri; 502.0 ± 220.1, 19 öğrenciden oluşan Tenis Grubunun Günlük Kalsiyum Tüketimi Değerleri; 726.0 ± 336.7 olarak ortalama değerleri bulunmuştur. 22 öğrenciden oluşan Kontrol Grubunun Dominant olmayan koldaki SOS ölçümleri; 3704 ± 147 ve Z skorları; -0.1 ± 1.2, 19 öğrenciden oluşan Yüzme Grubunun Dominant olmayan koldaki SOS ölçümleri; 3773 ± 81.0 ve Z skorları; -0.2 ± 0.8, 20 öğrenciden oluşan Hentbol Grubunun Dominant olmayan koldaki SOS ölçümleri; 3682 ± 87 ve Z skorları; -1.3 ± 0.8 ,19 öğrenciden oluşan Tenis Grubunun Dominant olmayan koldaki SOS ölçümleri; 3716 ± 82.6 ve Z skorları; -0.8 ± 0.8 olarak ortalama değerleri bulunmuştur. 22 öğrenciden oluşan Kontrol Grubunun Tibia SOS ölçümleri; 3678 ± 70 ve Z skorları; 0.3 ± 0.7, 19 öğrenciden oluşan Yüzme Grubunun Tibia SOS ölçümleri; 3688 ± 67.3 ve Z skorları; 0.2 ± 0.7, 20 öğrenciden oluşan Hentbol Grubunun Tibia SOS ölçümleri; 3558 ± 95.7 ve Z skorları; -0.1 ± 1.0, 19 öğrenciden oluşan Tenis Grubunun Tibia SOS ölçümleri; 3653 ± 63.4 ve Z skorları; -0.3 ± 0.7 olarak ortalama değerleri bulunmuştur. Yüzme, hentbol ve tenis gruplarının boy ortalama değerleri, kontrol grubunun boy ortalama değerlerinden yüksek bulunmuştur (p < 0,01). Yüzme, hentbol ve tenis gruplarının ağırlık ortalama değerleri, kontrol grubunun boy ortalama değerlerinden yüksek bulunmuştur (p < 0,01). Yüzme, hentbol, tenis ve kontrol gruplarının, günlük kalsiyum miktarları ortalama değerleri ile vücut yağ yüzdeleri ortalama değerleri arasında farklılık gözlemlenmemiştir (p > 0,05). Yüzme, hentbol, tenis ve kontrol gruplarının, dominant olmayan kol radius SOS ortalama değerlerinin karşılaştırılmasında farklılık gözlemlenmemiştir (p > 0,05). Yüzme, kontrol ve tenis gruplarının tibia SOS ortalama değerleri, hentbol grubunun tibia SOS ortalama değerlerinden yüksek bulunmuştur (p < 0,03). THE EVAULATION OF BONE MINERAL DENSITY OF CHILDREN INVOLVED IN DIFFERENT SPORT ACTIVITIES Adı ve Soyadı: ELİF ÇETİNER Danışmanın Adı: YRD.DOÇ.DR. İLHAN ODABAŞ EYLÜL 2002 SANS BEDEN EĞİTİMİ VE SPOR SUMMARY The aim of the studies is to evaluate the bone mineral density of the pre-adolescent children (girls-boys) who are engaged with different sports activities such as swimming tennis and handball. A total of 80 healthy non puberty children (40 girls-40 boys) born in 1994-1995 participated at the research. Group engaged in sports consisted of 60 children (20 children in averege for each group) who are regularly trained for at least a year (minimum twice a week) and control group consisted of 20 sedentary children. Height, weight, % fat and bone mineral densities of the children were measured and the daily calcium intakes were also determined by a questionnaire. Stadiometer for height, digital scale for weight, skinfold callipers and bioelectrical impedance methods for % fat and ultrasonografy methods (Sunlight Omnisense 7000p-SOS) for bone density measurements were utilized. Measurements were taken from the radius and tibia bones of the non doinant group. Fat measurments % which are made with skinfold kaliper; Triceps , Biceps , Subscapular and Superiliac taking the under skin fat thickness calculated with the % Durnin Womersley fat formula by taking into the consendiraton of dominand side. Density of bone mineral measurments done from sides which are not dominand radius and tibia bones. Moderations done after the approve of ethics council of specialist doctors at the Marmara University. The average value of the height measure for Control group which is consists of 22 students is found as: 134.5 ± 4.8. The average value of the height measure for swimming group which is consists of 19 students is found as 139.2 ± 5.9. The average value of the height measure for handball group which is consists of 20 students is found as 142.4 ± 5.09. The average value of the height measure for tennis group which is consists of 19 students is found as 139.5 ± 5.4. The average value of the weight measure for control group which is consists of 22 students is found as 30.5 ± 4.8. The average value of the weight measure for swimming group which is consists of 19 students is found as 34.0 ± 5.8. The average value of the weight measure for handball group which is consists of 20 students is found as 37.5 ± 7. The average value of the weight measure for Tennis group which is consists of 19 students is found as 33.7 ± 3.9. The BIA measure for control group which is consists of 22 students is found as: 13.5%. The BIA measure for swimming group which is consists of 19 students is found as 16.1%. The BIA measure for handball group which is consists of 20 students is found as: % 16.6. The BIA measure for tennis group which is consists of 19 students is found as: and 12.7 %. The DW measure for control group which is consists of 22 students is found as: 20.7%. The DW measure for swimming group which is consists of 19 students is found as 20.1%. The DW measure for handball group which is consists of 20 students is found as: 22.3%. The DW measure for tennis group which is consists of 19 students is found as: and 20.77 %. The daily calcium consumption of the control group which is consists of 22 students is found as; 689.2 ± 187.7 mg. The daily calcium consumption of the swimming group which is consists of 19 students is found as; 635.2 ± 262.3 mg. The daily calcium consumption of the handball group which is consists of 20 students is found as 502.0 ± 220.1 mg. The daily calcium consumption of the tennis group which is consists of 19 students is found as 726.0 ± 336.7 mg. The average values of SOS measures in the non-dominant arm and the Z scores of the Control group which is consists of 22 students are found as; 3704 ± 147 and -0.1 ± 1.2, respectively. The average values of SOS measures in the non-dominant arm and the Z scores of the swimming group which is consists of 19 students are found as; 3773 ± 81.0 and -0.2 ± 0.8, respectively. The average values of SOS measures in the non-dominant arm and the Z scores of the Handball group which is consists of 20 students are found as; 3682 ± 87 and -1.3 ± 0.8 , respectively. The average values of SOS measures in the non-dominant arm and the Z scores of the Tennis group which is consists of 19 students are found as; , 3716 ± 82.6 and -0.8 ± 0.8 , respectively. The average values of Tibia SOS measures and the Z scores of the control group which is consists of 22 students are found as; 3678 ± 70 and 0.3 ± 0.7, respectively. The average values of Tibia SOS measures and the Z scores of the swimming group which is consists of 19 students are found as; 3688 ± 67.3 and 0.2 ± 0.7, respectively. The average values of Tibia SOS measures and the Z scores of the handball group which is consists of 20 students are found as; 3558 ± 95.7 and -0.1 ± 1.0, respectively. The average values of Tibia SOS measures and the Z scores of the tennis group which is consists of 19 students are found as; 3653 ± 63.4 and -0.3 ± 0.7, respectively. The results showed that the average height values of the swimming, handball and tennis groups are higher than the average height of the control group (p < 0,01). The average weight values of the swimming, handball and tennis groups are higher than the average weight of the control group (p < 0,01). No difference between the average values of the daily calcium quantities and the average values of the body fat percentage was observed (p > 0,05). When non dominant arm radius SOS average values of the swimming, handball and tennis control groups were compared no difference was observed (p > 0,05). Tibia SOS average values of the swimming, control and tennis groups were found to be higher than the tibia SOS average values of the handball group (p < 0,03).
Keywords: Kemik Yoğunluğu_Çocuklarda; Mineral Yoğunluğu_Çocuklarda